Macroprolactinomas and Nonfunctioning Pituitary Adenomas and Pregnancy Outcomes. Issue 1 (January 2017) - Lambert, Kimberley; Rees, Kate; Seed, Paul T.; Dhanjal, Mandish K.; Knight, Marian; McCance, David R.; Williamson, Catherine
Abstract : OBJECTIVE: To examine the monitoring, management, and outcomes of pituitary tumors in pregnancy. METHODS: A national, prospective, observational, population-based case series study was conducted in all U.K. consultant-led obstetric units over 3 years using the U.K. Obstetric Surveillance System. To evaluate rates of adverse pregnancy outcomes, women with a macroprolactinoma (10 mm or greater) or nonfunctioning pituitary adenoma, diagnosed before or during pregnancy, were compared with two comparison groups: 1) a U.K. Obstetric Surveillance System cohort with singleton (n=2, 205) or twin (n=27) pregnancy; and 2) data from the Office of National Statistics (n=2, 703, 102). Main outcome measures were the incidence, management, and frequency of adverse maternal and offspring outcomes of pituitary tumors in pregnancy. RESULTS: There were 71 confirmed cases of pituitary tumors in pregnancy (49 macrolactinoma, 16 nonfunctioning adenomas, three acromegaly, three Cushing's disease). The women with pituitary tumors were 4 years older than comparison women ( P <.001). None of the nine women treated with surgery or radiotherapy before pregnancy had symptomatic tumor expansion. This occurred in 6 of 40 women with macroprolactinomas and one of seven nonfunctioning adenomas diagnosed before conception and in three of five women with nonfunctioning adenomas diagnosed in pregnancy. Two women had pituitary apoplexy, both of whom also had symptoms of expansion of tumor or surrounding pituitary tissue. To within the level of accuracy possible, there was no evidence that pituitary tumors were associated with adverse pregnancy outcomes (pregnancy-induced hypertension, preeclampsia, preterm labor, stillbirth). Women with nonfunctioning adenomas were more likely to have cesarean delivery compared with women in a control group (relative risk 2.06, confidence interval 1.26–3.36, P =.035). CONCLUSION: The majority of women with macroprolactinomas and nonfunctioning adenomas have good pregnancy outcomes. Nonfunctioning pituitary adenomas occur more commonly in pregnancy than previously thought and can present de novo with symptoms of pituitary expansion in pregnancy. Abstract : Macroprolactinoma and nonfunctioning pituitary adenoma can present in pregnancy with expansion and apoplexy but typically respond to medical management with good pregnancy outcomes.